Surgical Management of a Locally Advanced Symptomatic Recurrence of Penile Sarcoma Secondary to Prostate Brachytherapy - Hakky,Tariq S. (2013)
Background The surgical management of patients with symptomatic metastatic or locally advanced recurrences involving the penis remains poorly characterized. The aim of the present abstract and video is to detail our experience in the surgical management of a specific patient with a locally advanced symptomatic recurrence of penile sarcoma secondary to prostate cancer treated with primary brachytherapy. Materials and Methods A 70 year old male patient initially treated for localized prostate cancer with interstitial brachytherapy at an outside facility developed an unfortunate secondary malignancy consisting of a locally advanced penile sarcoma involving as well the prostate and base of the bladder. Despite our best efforts to control his pain, he developed a very symptomatic local recurrence with a secondary penile abscess and purulent periurethral drainage. At this time, it was felt a surgical resection consisting of a total penectomy, urethrectomy, cystoprostatectomy, and ileal conduit urinary diversion would be the best option for local cancer control in this particular patient. Results The patient underwent the surgical resection without any complications as illustrated in this surgical video, with a jejunal intestinal mass identified at the time of surgery which was resected with a primary bowel anastomosis performed. The patient was discharged from hospital uneventfully with his symptomatic local recurrence being successfully managed and the patient no longer requiring oral narcotics for pain control. The pathological report confirmed a locally advanced sarcoma involving the penile, prostate, and bladder which was resected with negative surgical margins and the jejunal mass was confirmed to represent a small bowel sarcoma metastatic site. Conclusion As highlighted in the present video, the treatment of a symptomatic sarcoma local recurrence contiguously involving the penis can be successfully managed provided the patient is informed of the potential morbidity and psychosocial implications imparted by performing a total penectomy and adjacent organ resection.